Validation of Grobman's graphical nomogram for prediction of vaginal delivery in Indian women with previous caesarean section - Mahak Bhardwaj; Shalini Gainder; Seema Chopra; Rashmi Bagga; Shiv Sajan Saini (Elsevier, 2023)
Purpose: To validate Grobman's nomogram for prediction of trial of labour after caesarean section (TOLAC) success in the Indian population. Methods: A prospective observational study of women with previous lower segment caesarean sections (LSCS) who were admitted for TOLAC between January 2019 and June 2020 at a tertiary care hospital We compared the Grobman's predicted VBAC success probability to the observed VBAC rate in the study population and devised a receiver-operator characteristics (ROC) curve for the nomogram. Results: Among the 124 women with prior LSCS who chose TOLAC and were included in the study, 68 (54.8%) had a successful VBAC and 56 (45.2%) had a failed TOLAC. The mean Grobman's predicted success probability for the cohort was 76.7%, significantly higher in VBAC women versus CS women (80.6% vs. 72.1%; p 0.001). The VBAC rate was 69.1% with a predicted probability of > 75% and only 42.9% with a probability of 50%. Women in the > 75% probability group had a nearly similar observed and predicted VBAC rate (69.1% vs. 86.3%; p = 0.002), and a greater number of women in the 50% probability group had successful VBAC than predicted (42.9% vs. 39.5%; p = 0.018). The area under the ROC curve for the study was 0.703 (95% CI 0.609-0.797; p 0.001). Grobman's nomogram had a sensitivity of 57.35%, a specificity of 82.14%, a positive predictive value (PPV) of 79.59%, and a negative predictive value (NPV) of 61.33% at a predicted probability cut-off of 82.5%. Conclusions: Women who had a higher Grobman's predicted probability had greater VBAC success rates than those with low predicted probability scores. The prediction ability of the nomogram was highly accurate at higher predicted probabilities, and even at lower predicted probabilities, women did have good odds of delivering vaginally.